Taking Advantage of the Selectivity of Histone Deacetylases and Phosphodiesterase Inhibitors to Design Better Therapeutic Strategies to Treat Alzheimer’s Disease - Cuadrado-Tejedor, Mar; Pérez-González, Marta; García-Muñoz, Cristina; Muruzabal, Damián; García-Barroso, Carolina; Rabal, Obdulia; Segura, Víctor; Sánchez-Arias, Juan A.; Oyarzabal, Julen; Garcia-Osta, Ana (Frontiers in Aging Neuroscience, 2019)
The discouraging results with therapies for Alzheimer´s disease (AD) in clinical trials, highlights the urgent need to adopt new approaches. Like other complex diseases, it is becoming clear that AD therapies should focus on the simultaneous modulation of several targets implicated in the disease. Recently, using reference compounds and the first-in class CM-414, we demonstrated that the simultaneous inhibition of histone deacetylases (class I HDACs and HDAC6) and phosphodiesterase 5 (PDE5) has a synergistic therapeutic effect in AD models. To identify the best inhibitory balance of HDAC isoforms and PDEs that provides a safe and efficient therapy to combat AD, we tested the compound CM-695 in the Tg2576 mouse model of this disease. CM-695 selectively inhibits HDAC6 over class I HDAC isoforms, which largely overcomes the toxicity associated with HDAC class 1 inhibition. Furthermore, CM-695 inhibits PDE9, which is expressed strongly in the brain and has been proposed as a therapeutic target for AD. Chronic treatment of aged Tg2576 mice with CM-695 ameliorates memory impairment and diminishes brain Aβ, although its therapeutic effect was no longer apparent 4 weeks after the treatment was interrupted. An increase in the presence of GRP78 and Hsp70 chaperones may underlie the therapeutic effect of CM-695. In summary, chronic treatment with CM-695 appears to reverse the AD phenotype in a safe and effective manner. Taking into account that AD is a multifactorial disorder, the multimodal action of these compounds and the different events they affect may open new avenues to combat AD.